Principles Of Competence and Practical Reflection (Eurasian Journal of Learning and Academic Teaching, 2022)
The presented Graduation Project Work focuses on the deep understanding of CLT approach in the field of English Language Teaching field in the Uzbekistan context. The paper is written in good English and presents the views, analysis of teaching based on the experiences of the author. The project work consists of 20 homework tasks that come from the course book “Reconceptualizing Language Teaching: an In-service Teacher Education Course in Uzbekistan” written in collaboration with Uzbek and American educators. The content of the paper follows the order of the given homework tasks that illustrate the understanding of the author about the implementation of CLT in teacher’s context